Gut transcriptomic changes during hibernation in the greater horseshoe bat (Rhinolophus ferrumequinum) - Sun, Haijian (Front Zool, 2020)
BACKGROUND: The gut is the major organ for nutrient absorption and immune response in the body of animals. Although effects of fasting on the gut functions have been extensively studied in model animals (e.g. mice), little is known about the response of the gut to fasting in a natural condition (e.g. hibernation). During hibernation, animals endure the long term of fasting and hypothermia. RESULTS: Here we generated the first gut transcriptome in a wild hibernating bat (Rhinolophus ferrumequinum). We identified 1614 differentially expressed genes (DEGs) during four physiological states (Torpor, Arousal, Winter Active and Summer Active). Gene co-expression network analysis assigns 926 DEGs into six modules associated with Torpor and Arousal. Our results reveal that in response to the stress of luminal nutrient deficiency during hibernation, the gut helps to reduce food intake by overexpressing genes (e.g. CCK and GPR17) that regulate the sensitivity to insulin and leptin. At the same time, the gut contributes energy supply by overexpressing genes that increase capacity for ketogenesis (HMGCS2) and selective autophagy (TEX264). Furthermore, we identified separate sets of multiple DEGs upregulated in Torpor and Arousal whose functions are involved in innate immunity. CONCLUSION: This is the first gut transcriptome of a hibernating mammal. Our study identified candidate genes associated with regulation of food intake and enhance of innate immunity in the gut during hibernation. By comparing with previous studies, we found that two DEGs (CPE and HSPA8) were also significantly elevated during torpor in liver and brain of R. ferrumequinum and several DEGs (e.g. TXNIP and PDK1/4) were commonly upregulated during torpor in multiple tissues of different mammals. Our results support that shared expression changes may underlie the hibernation phenotype by most mammals.